Análise dos resultados de ceratectomia fotorrefrativa com mitomicina C e LASIK para correção miópica - Wallau, Anelise Dutra [UNIFESP] (2010)
Purpose: To compare visual acuity results, cycloplegic refraction, aberrometry and contrast sensitivity in eyes that underwent photorefractive keratectomy (PRK) with mitomycin C (MMC) or laser in situ keratomileusis (LASIK) for wavefront-guided myopic corrections during one year follow-up. To evaluate slit-lamp microscopy in both groups during follow-up. To evaluate subjective pain, visual complains and satisfaction with visual results in the two groups during follow-up. To analyse specular microscopy values before and six months after surgeries in both groups. To compare biomechanical properties of the cornea in the two groups one year after surgeries. Methods: Forty-four patients (88 eyes) with moderate myopia and an estimated ablation depth greater than 50 μm using the LADARWave 4000 (Alcon Laboratories) platform in both eyes were randomized to receive LASIK in one eye and PRK with application of MMC 0.002% for one minute in the fellow eye in wavefront-guided surgeries. Corneal topography (EyeSys 2000, EyeSys and Orbscan II, Orbtek/Bausch & Lomb), uncorrected visual acuity (UCVA, Early Treatment Diabetic Retinopaty Study table), cycloplegic refraction, best spectacle-corrected visual acuity (BSCVA), aberrometry (LADARWave 4000), central ultrasound corneal pachymetry (Sonogage Inc) and a comprehensive ophthalmologic examination were performed before surgeries and at one, three, six and twelve months postoperative visits. Photopic and mesopic contrast sensitivity (Optec 6500, F.A.C.T.; Stereo Optical Co) with BSCVA was performed in both eyes before surgeries and at three, six and 12 months follow-up. A subjective pain questionnaire was applied at early postoperative visits and another visual complain and satisfaction questionnaire with surgery in each eye was applied one, three, six and twelve months after surgical procedures. Slit-lamp anterior segment microscopy was performed at early postoperative visits and at follow-up visits always as the last examination (blind examiner for surgical procedure). Specular microscopy (Topcon SP 2000p, Topcon) was performed before and six months after surgeries. Biomechanical properties of the cornea (ORA, Reichert) were evaluated one year after surgeries. The tests ANOVA for repeated measures and the student’s t test were used for statistical analyses. Results: The mean age was 31.7 years (range, 21-54 years). There was no statistically significant between-group difference in UCVA, BSCVA, aberrometry, contrast sensitivity or specular microscopy before surgeries. The mean attempted spherical equivalent (SE) was - 3.99±1.20 diopters (D) in LASIK eyes and - 3.85±1.12 D in PRK with MMC eyes (p>0.05). The mean ablation depth was 73.09±14.55 μm and 70.70±14.07 μm in LASIK and PRK with MMC eyes, respectively (p>0.05). Forty-two patients (95.5%) completed one year follow-up. The PRK with MMC eyes presented statistically significant better mean UCVA values than LASIK eyes at three, six and 12 months visits. The mean BSCVA was also statistically significant better in PRK with MMC eyes than in LASIK eyes one year after surgeries (p<0.05). There was no between-groups statistical difference in SE during one year follow-up. All PRK with MMC eyes reepithelialized within five days after surgical procedure and no eye presented more than grade 1 haze (Fantes scale). The LASIK eyes presented statistically significant higher lower and higher order aberrations values than PRK with MMC eyes during follow-up (p<0.05). The PRK with MMC group showed better results in photopic and mesopic contrast sensitivity than LASIK eyes during one year follow-up (p<0.05). Until the fifth postoperative day, PRK with MMC eyes presented higher pain scores than LASIK eyes. PRK with MMC eyes were better rated in terms of subjective visual symptoms and visual satisfaction. There were no statistical differences between the groups in specular microscopy (p>0.05). LASIK eyes showed statistically significant higher corneal resistance factor (CRF) and corneal hysteresis (CH) values than PRK with MMC eyes (p<0.05). Conclusions: The PRK with MMC eyes presented better UCVA, BSCVA, better correction of lower order aberrations and lower higher order aberration values than LASIK eyes. It also showed better contrast sensitivity results and was better rated in terms of visual satisfaction. There was no clinically significant haze in PRK with MMC eyes. The PRK with MMC eyes presented higher pain scores at early postoperative visits. There was no between groups differences in specular microscopy. LASIK eyes presented higher CRF and CH values one year after surgeries.